Site quality assessment for Pinus sylvestris L. in mixed forests of the central part of "Rhodope Mountains" in northeastern Greece - Milios, Elias; Kitikidou, Kyriaki; Pipinis, Elias; Stampoulidis, Athanasios; Akritidou, Sofia; Smiris, Pavlos (Annals of Silvicultural Research, 2018)
In this work, site index curves are developed for Pinus sylvestris in Greece, because of the ecological, social and economic importance of the species. Data from the forest of the Central Rhodope Mountains of north-eastern Greece are used. Thirty one dominant trees, which had the mean height of the 100 tallest trees per hectare were randomly selected and cut, in the 1990s. For each sampled tree a stem analysis was conducted. The selected height-age model for Pinus sylvestris was . The mean annual increment from stem analyses was equal to 0.212 m, corresponding to a base age of 68 years. The height estimation, calculated by the selected model, for a 68 year-old tree, is 23 m (SI23). Using the quadratic model as the guide curve for the development of anamorphic site index curves, we produced two more curves, SI20 and SI27. The main findings of this research are that Pinus sylvestris seems to grow faster in height in the productive site of the present study compared with that of Sweden, its growth is similar to that of the two most productive sites in forests in northwestern Spain, and it seems comparable to the fairly productive sites of northwestern Turkey.